EXAMINING THE RELATIONSHIP BETWEEN FINANCIAL RATIOS AND STOCK RETURNS: A STUDY IN THE FOOD SECTOR (Third Sector Social Economic Review, 2022)
Most of studies in the literature, it is assumed that there is a relationship between stock returns and financial ratios. From this point of view, the aim of this study is to determine the relationship between stock returns and financial ratios. The scope of the study consists of food companies operating in Borsa Istanbul in the period of 2009-2019. The dependent variable of the study is the annual average stock returns. The independent variables consist of six financial ratios: cash ratio, inventory turnover, asset turnover, fixed asset turnover, short-term liabilities/total liabilities and return on equity. Multiple regression analysis and correlation were applied in empirical analysis. According to the findings obtained from the study, it was concluded that the cash ratio, inventory turnover, asset turnover and fixed asset turnover affect the stock returns of the companies.
Keywords: Stock Returns; Financial Ratios; Borsa İstanbul; Regression Analysis; Food Sector